PENGARUH PELAKSANAAN KINERJA PENGAWAS PAI DAN KEPALA SEKOLAH TERHADAP PROFESIONALITAS GURU PAI DI SMP NEGERI 1 PAREPARE - Andi Syamsul (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
This article aims to discuss the implementation of the supervisory duties of the PAI, the performance of principals, the professionalism of PAI teachers, and the contribution of supervisors and principals to the professionalism of PAI teachers in SMP Negeri 1 Parepare. This type of research is applied research that is correlational or associative. The PAI surveillance population, the principals of one person and the PAI teacher are four. Sampling technique used is saturated sample technique or total sampling that is the determination and sampling taken as a whole as many as 6 people. The results show that the implementation of PAI supervisors in SMPN 1 Parepare is very high. The performance of principals is categorized as either high or good. The professional level of teachers of PAI is categorized as high, strong or good professionalism of the teacher. As for the supervisors of PAI and principals there is a very significant influence on the professionalism of PAI teachers in SMP Negeri 1 Parepare.